2004
DOI: 10.1002/polb.20089
|View full text |Cite
|
Sign up to set email alerts
|

Plastic deformation of glassy polystyrene: A unified model of yield and the role of chain length

Abstract: A study was made of yield and plastic flow in glassy polystyrene. A range of 12 linear atactic polystyrenes was studied: monodisperse, bimodal blends, and a polydisperse commercial sample. M n varied between 66,000 and 490,000 g/mol. These were given standardized thermal treatments and then subjected to uniaxial compression tests in the glassy state over the temperature range 40 to 95°C and nominal strain-rates 10 Ϫ4 to 10 Ϫ3 s Ϫ1 . Their constitutive responses were interpreted in terms of the physically based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 16 publications
3
81
0
Order By: Relevance
“…The reason for the deviation is that the deformation conditions are not the same: experiments have a much slower strain rate ͑thereby lowering the yield stress; experimentally it is observed that the yield stress has a logarithmic dependence on the strain rate 49 ͒, slower cooling rate ͑resulting in a higher yield stress 50 ͒, and longer chain lengths ͑increasing the yield stress due to the slower relaxation of the middle of the chain compared to the chain ends 57 ͒. Despite these quantitative differences, the results show qualitatively the same behavior.…”
Section: A Compression and Extensionmentioning
confidence: 99%
“…The reason for the deviation is that the deformation conditions are not the same: experiments have a much slower strain rate ͑thereby lowering the yield stress; experimentally it is observed that the yield stress has a logarithmic dependence on the strain rate 49 ͒, slower cooling rate ͑resulting in a higher yield stress 50 ͒, and longer chain lengths ͑increasing the yield stress due to the slower relaxation of the middle of the chain compared to the chain ends 57 ͒. Despite these quantitative differences, the results show qualitatively the same behavior.…”
Section: A Compression and Extensionmentioning
confidence: 99%
“…[4][5][6][7][8][9] These plastic instabilities are the same as those found for short-term failure, observed in tensile testing under constant strain rate. 10 In the last 15 years, a lot of effort has been invested by a number of groups at different universities into the development and validation of 3D constitutive models that can describe this localization behavior of glassy polymers, for example, in the group of Mary Boyce at MIT, [11][12][13] the group of Paul Buckley in Oxford [14][15][16] and in our Eindhoven group. [17][18][19] It was shown in subsequent quantitative studies 10,[19][20][21][22][23][24] that it is the large strain intrinsic behavior (yield, strain softening, and subsequent strain hardening) of the polymer that determines the macroscopic localization behavior, and thus failure.…”
Section: Introductionmentioning
confidence: 99%
“…From Figure 1a it is clear that an increase of yield stress, due to a thermal treatment, will directly imply an increase in strain softening. The influence of molecular weight on the intrinsic response is usually small and negligible [20,22], which makes thermal history the key factor in influencing the intrinsic properties of a specific polymer glass. The thermal history is also reflected in the long-term failure behavior of polymer glasses.…”
Section: Phenomenologymentioning
confidence: 99%
“…Especially in the case of amorphous polymer glasses considerable effort has been directed towards the development of 3D constitutive models that were capable to capture the experimentally observed intrinsic behavior, e.g. in the group of Mary Boyce at MIT [15][16][17], the group of Paul Buckley in Oxford [18][19][20], and in our Eindhoven group [21][22][23]. These developments enabled a quantitative analysis of localization and failure in polymer glasses [22,[24][25][26][27][28][29], and revealed the crucial role of the intrinsic post-yield characteristics on macroscopic strain localization.…”
Section: Introductionmentioning
confidence: 99%